FAKTOR-FAKTOR INFLUENCE DAN EFFI- CIENCY YANG MEMPENGARUHI REPURCHASE INTENTION - ina Oktaviana; Roger Wirawan (Media Riset Bisnis & Manajemen, 2004)
Social interaction between customers and employees and customer convenience are con- sidered an an imporlant for restaurant business success. The study investigates the influ- ence of customer comfort, employee job enthusiasm and customer convenience as determi- nants of repurchase intention. Study was conducted on customers of Chopstix restaurant in Jakarta, the data are analyzed by multiple regression analyis. Results confirmed that social comfort positively influence repurchase intention, but no significant relationship observed of employee job enthusiasm and customer convenience.